EFEK KOMPOSISI PARAFIN DAN MALAM LEBAH TERHADAP EKSPANSI TERMAL LINIER MALAM MODEL: EFFECT PARAFFIN AND BEESWAX RATIO TO LINEAR EXPANSION OF MODELLING WAX - Fitri Isnaini; Dyah Irnawati; Widowati Siswomihardjo (Dentika: Dental Journal, 2009)
Modelling wax is a pattern wax for complete denture fabrication. It consists of various waxes and other components. Thecomposition influenced the physical properties of modelling wax. The objective of this study was to examine the effect ofparaffn to beeswax ratio on the linear thermal expansion (LTE) of modelling wax. The modelling waxes consist of paraffin (Pertamina, Kalimantan), beeswax (SEA, Yogyakarta), carnauba wax (PT Bratachem, Indonesia), and dammar(Kalimantan). Five compositions of waxes were made with different paraffin to beeswax ratio (paraffin: beeswax: carnauba wax: dammar in % weight): K1 = 70:20:4:6, K2 = 72.5:17,5:4:6, K3 = 75:15:4:6, K4 = 77.5:12.5:4:6, and K5 =80:10:4:6. Six specimens (305 x 22.2 x 14.3 mm) were made of each composition. The specimens were immersed inbathing water at 25Â°C and 40Â°C for 20 minutes, and the specimen length was measured by travelling microscope aftereach immersion. The percentage of the LTE was measured. Data were analyzed by one-way Anova and LSD0.05. Theresults showed that the LTE of modelling waxes was between 0.27 + 0.02 % (70:20 ratio) and 0.73 + 0.06 % (80:10ratio). The Paraffin to beeswax ratio influenced the LTE of modelling waxes and showed the significant differencesbetween all compositions (p<0.5). As conclusion, the paraffin to beeswax ratio influenced the linear thermal expansion ofmodelling wax.